Failed induction of labor and associated factors in Adama Hospital Medical College, Oromia Regional State, Ethiopia. (March 2022) - Demssie, Enku Afework; Deybasso, Haji Aman; Tulu, Tewodros Mengistu; Abebe, Dawit; Kure, Mohammed Abdurke; Teji Roba, Kedir
Background: Failed induction of labor continues to be a public health challenge throughout the world. This failed induction of labor is associated with a higher rate of maternal and fetal morbidity because it increases the unwanted effect of emergency cesarean section. It is also associated with an increased risk of numerous adverse maternal and perinatal outcomes such as uterine rupture, nonreassuring fetal heart rate tracing, postpartum hemorrhage, stillbirth, and severe birth asphyxia. Thus, this study was aimed to assess the failed induction of labor and associated factors in the Adama Hospital Medical College, Oromia Regional State, Ethiopia. Methods: A facility-based cross-sectional study was conducted from 1 to 30 December 2020 in Adama Hospital Medical College, Ethiopia. A total of 379 women who underwent labor induction in the Adama Hospital Medical College from December 2019 to November 2020 were enrolled in the study. The participants' charts were selected using a simple random sampling technique. Data were collected using a pretested and validated structured questionnaire. Descriptive statistics were carried out using frequency tables, proportions, and summary measures. Predictors were assessed using a multivariable logistic regression analysis model and reported using adjusted odds ratio with 95% confidence interval. Statistical significance was considered at a p value <0.05. Results: Of 379 induced labor included in the study, the proportion of failed induction was found to be 29.6% (95% confidence interval (25.2, 34.3)). Prelabor rupture of the membrane was found to be the most common indication for induction of labor (46.4%) followed by a hypertensive disorder of pregnancy (21.6%). In the final model of multivariable analysis, predictors such as: nulliparity (adjusted odds ratio = 2.32, 95% confidence interval (1.08, 5.02)), unfavorable cervical status (adjusted odds ratio = 3.46, 95% confidence interval (1.51, 7.94)), prelabor rupture of membrane (adjusted odds ratio = 2.60, 95% confidence interval (1.14, 5.91)), hypertensive disorder of pregnancy (adjusted odds ratio = 3.01;95% confidence interval (1.61, 558)), preinduction membrane status (adjusted odds ratio = 3.63; 95% confidence interval (1.48, 8.86)), and birth weight of greater than 4000 g (adjusted odds ratio = 4.33; 95% confidence interval (1.44, 13.02)) were statistically associated with failed induction of labor. Conclusion: The prevalence of failed induction of labor was relatively high in this study area because more than a quarter of mothers who underwent induction of labor had failed induction. This calls for all stakeholders to adhere to locally available induction protocols and guidelines. In addition, pre-induction conditions must be a top priority to improve the outcome of induction of labor.